PENGULATAN EMOSI DAN TRAUMA TOKOH UTAMA NOVEL TENTANG KAMU KARYA TERE LIYE PENDEKATAN PSIKOLOGI SASTRA - Fitri, Fitri; Jelita, Jelita; Stefani Anisa; Wahida, Wahida; Saptiana Sulastri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the emotional struggles and trauma experienced by the main character in the novel Tentang Kamu by Tere Liye using a literary psychology approach. The research method used is descriptive qualitative with data collection techniques in the form of library research and text analysis, while data analysis is conducted through identification and interpretation of the emotional aspects and traumatic experiences of the main character. The results show that the main character experiences sadness, loss, fear, and psychological pressure due to past trauma; however, the character also demonstrates strong resilience that enables them to rise and find meaning in life.